Improving Sleep Attributes of Military Personnel in Operational Settings by Controlling Exposure to Blue Light. (September 2017) - Ryan, Alex; Matsangas, Panagiotis; Anglemyer, Andrew; Shattuck, Nita Lewis
Military members often work in challenging environments. Their sleep is degraded by extended operational commitments and the requirement to work in shifts. Exposure to light at circadian inappropriate times may also have a detrimental impact on service members' sleep, fatigue levels, and mood. This two-week field study assessed whether sleep-related attributes can be improved by limiting exposure to blue light prior to sleep. Participants (N=30) were observed for one week without using blue light blocking glasses followed by a second week when they used blue light blocking glasses for two hours prior to their bedtimes. Sleep was assessed with wristworn actigraphy. Daytime sleepiness decreased (p=0.011), and mood improved (p<0.001) after wearing the glasses. Insomnia symptoms decreased while sleep onset latency and sleep quality improved, although not at statistically significant levels. These findings suggest that controlling exposure to blue light for two hours prior to sleep has a beneficial effect on sleep quality and mood.